Penatalaksanaan Terapi Latihan Untuk Anak Developmental Delay Di Griya Fisio Bunda Novy Yogyakarta - Krisdiyanti, Nina, Umi Budi Rahayu, S.Fis, S,Pd, M.Kes (2015)
Background: Not all of children in grow and develop will always a normal state. A Child with development motor delay was expected can still be with done and right psychotherapy management, so a child can be increased in development motor. A method of exercise was one method to help improve motor skills for a child developmental delay. Purpose of research ws to know benefits of exercise to increase functional activity of patient was like stand and walk in case of developmental delay. A method of research was descriptive. Instrument used exercise extensor flexsor knee and exercise , kneeling of crawling exercise, bolsters sit on exercise, exercise a balance on the ball performed as many as 6 times the exercise.T he results of the exercise and assessment motor skills with DDST II. Results of exercise on shoulder, elbow, wrist, hip, knee, ankle showing with power of normal. Conclusions: Muscle power by using children memorial hospital (CMH), not change in value of muscle power from T0 until T5 and still normal